Hubungan Profitabilitas, Ukuran Perusahaan, dan Kualitas Audit pada Nilai Perusahaan: Studi Empiris pada Perusahaan Makanan dan Minuman di Bursa Efek Indonesia Periode (2019 – 2023) - I Wayan Pradnya Ari Suta; I Made Karya Utama (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the relationship between profitability, firm size, and audit quality and firm value in food and beverage companies listed on the Indonesia Stock Exchange during the 2019–2023 period. Firm value is proxied by Price to Book Value (PBV), profitability is measured using Return on Assets (ROA), firm size is measured by the natural logarithm of total assets, while audit quality is proxied by the auditor’s opinion. This study employs a quantitative associative approach using secondary data obtained from annual financial statements and independent audit reports. The research sample consists of 19 food and beverage companies, resulting in 95 firm-year observations, selected using purposive sampling. Data analysis techniques include descriptive statistics, classical assumption tests, multiple linear regression analysis, and hypothesis testing using SPSS version 25. The results show that profitability, firm size, and audit quality simultaneously have a significant effect on firm value. However, partially, profitability, firm size, and audit quality do not have a significant effect on firm value. These findings indicate that investors in the food and beverage sector do not rely solely on profitability, company size, or auditor opinions when assessing firm value, but also consider other factors such as growth prospects, business stability, and long-term managerial strategies. This study is expected to contribute to the literature on firm value and provide practical implications for management and investors in investment decision-making.